Reproductive strategy of Oreochromis niloticus (Pisces: Cichlidae) in Opa reservoir, Ile-Ife, Nigeria - Komolafe, O.O. (2007)
The fish family Cichlidae has a large diversity and dominates African freshwater bodies, with over 200 species reported in inland waters. Sampling for the fish Oreochromis niloticus (Linnaeus) in Opa reservoir, Nigeria, started in October 1997 and extended until February 2000. The fishing methods employed for collecting the 1 430 specimens were cast netting and gillnetting. Egg diameter varied between 2.12 mm and 2.69 mm with a mean of 2.47±0.02. Female gonadosomatic index was 1.34±0.01 (0.12-4.06, n= 637). The male gonadosomatic index was 0.39±0.02 (0.03-1.67, n= 789). In Opa reservoir, O. niloticus bred throughout the study period. The species was a maternal mouth brooder with the female fish carrying eggs and fry in the buccal cavities. The sex ratio of O. niloticus was approximately 1:1 in the reservoir. The fecundity of the species was between 73 eggs and 1 810 eggs per female with a mean fecundity of 815 eggs.